PENGEMBANGAN MEDIA MAZE HURUF VOKAL UNTUK KEMAMPUAN BERPIKIR SIMBOLIK ANAK USIA 5–6 TAHUN - Shanda Agusti Ramadani; Akmilah Ilhami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a valid, practical, and effective vowel maze media in improving the symbolic thinking skills of children aged 5–6 years. This research is motivated by the limitations of interactive learning media in schools, so that children do not get an interesting learning experience in recognizing vowels. The research method uses the Rowntree development model which includes the planning, development, and evaluation stages, and is equipped with Tessmer formative evaluation through expert review, one-to-one evaluation, and small group evaluation. The research subjects were 12 children, consisting of 3 children in the one-to-one evaluation stage and 9 children in the small group evaluation stage, while the object of the research was the vowel maze media in learning to recognize vowels. The research instruments included a material expert validation sheet, a media expert validation sheet, an observation sheet, and a teacher response questionnaire. The validation results showed that the vowel maze media was very valid with a score of 100% from material experts and 95% from media experts, so that the average validity reached 97%. The practicality test demonstrated excellent practicality, with scores of 91% in the one-to-one evaluation stage and 96% in the small group evaluation stage, or an average of 93%. Furthermore, the media proved effective in improving children's symbolic thinking skills in recognizing vowels, imitating letter shapes, naming objects that begin with vowels, and grouping objects based on the same vowel.